2011
DOI: 10.1007/s00259-010-1721-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of patient positioning aids on PET quantification in PET/MR imaging

Abstract: Depending on the size and density of the positioning aids used, a regionally variable underestimation of PET activity following AC is observed when positioning aids are not accounted for. This underestimation may become relevant in combined PET/MR imaging of patients with neuropsychiatric indications, but appears to be of no clinical relevance in imaging the extremities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 12 publications
0
29
0
Order By: Relevance
“…Therefore, in whole-body applications, AC methods that do not account for bone may be sufficient for a wide variety of clinical applications (10). In addition to generating a suitable map from the MR images, the attenuation of MRI radiofrequency coils and ancillary devices must also be accounted for (11,12).…”
mentioning
confidence: 99%
“…Therefore, in whole-body applications, AC methods that do not account for bone may be sufficient for a wide variety of clinical applications (10). In addition to generating a suitable map from the MR images, the attenuation of MRI radiofrequency coils and ancillary devices must also be accounted for (11,12).…”
mentioning
confidence: 99%
“…[33][34][35]44 A recent study demonstrated that reconstructed Combined PET/MRI for Improving Quantitative Imaging radioactivity concentrations in brain tissue from a combined UTE/Dixon 45 four tissue class attenuation correction approach correlated tightly (r 2 ¼ 0.99) with those produced using CT-based attenuation correction. 35 More recently, work has been presented on MR-based attenuation correction for whole body imaging, [46][47][48][49][50][51][52][53][54][55][56][57][58][59] including the impact of surface coils and truncation artifacts from a limited MR transaxial field-of-view. Non-rigid registration of MR to CT in order to produce a pseudo-CT from MR for attenuation correction was not found to be as successful as the aforementioned non-rigid approaches for MR-based attenuation correction in the brain.…”
Section: Attenuation Correctionmentioning
confidence: 99%
“…What is new compared with standalone MRI is that care has to be taken that any additional positioning aids do not result in significant attenuation of the 511-keV photons (14). In PET/MRI, surface coils are used to increase MRI image quality and reduce imaging time, just as in standalone MRI.…”
Section: In-bed Patient Preparationmentioning
confidence: 99%